Efek gel ekstrak daun kemangi (Ocimum sanctum l.) terhadap luas ulkus traumatikus pada Rattus norvegicus - Nikmatus Sa'adah; Hening Tuti Hendarti; Herlambang Prehananto; Bagus Soebadi; Eka Putri Pertiwi; Agus Aan Adriansyah (Jurnal Kesehatan Gigi, 2021)
Introduction: Traumatic ulcers are damage to the mucosal tissue of the oral cavity which causes some of the epithelial structures to be lost to exceed the basement membrane or even reach the lamina propia. The causes of ulcers is trauma, which can be physical, mechanical, thermal or chemical trauma. One of traditional treatments for traumatic ulcers is basil (Ocimum sanctum L.) leaves which contain such as alkaloids, saponins, flavonoids, and tannins as anti-inflammatory. This research was aimed to prove the effect of basil leaves (Ocimum sanctum L.) extract gel with a concentration of 0.5%, 1%, and 1.5% to traumatic ulcer area in Rattus norvegicus. Method: Laboratory experimental study with a post test only control group design. The basil leaves extract made into a gel concentration of 0.5%, 1, and 1.5%, and the control group using a CMC-Na gel, applied to Rattus norvegicus which had been made before by a traumatic ulcer. Traumatic ulcer area measurements using digital calipers on day 0, day 3, day 5, and day 7. The data were analyzed by oneway ANOVA test. Results: The significance value on one way anova test of research group was 0,000. Average traumatic ulcer area in research group smaller than control group. Conclusion: There was an effect of basil leaves (Ocimum sanctum L.) extract gel to traumatic ulcer area in Rattus norvegicus.